ABUNDANCE OF BENEFICIAL ARTHROPODS IN PESTICIDE SPRAYED AND UNSPRAYED BT COTTON AGRO-ECOSYSTEM OF KALABURAGI, KARNATAKA, INDIA - VENKATESHWAR, AMBRISHA; VIJAYKUMAR, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The unique abundance of beneficial arthropod communities in the cotton agro-ecosystem may be considered as an important natural resource as it plays a vital role in pest control. The heavy pesticide application reduces the ability of beneficial arthropods in regulating cotton pests. In the cotton agro-ecosystem both pests and beneficial arthropod fauna such as predators pollinators, parasitoids co-exist. However farmers utilizes heavy application of unsafe and indiscriminate pesticides which leads to disruption and loss of biological control agents such as pollinators and natural enemies. In the present study comparison of abundance of beneficial arthropod communities in pesticide sprayed and unsprayed Bt cotton fields of Kalaburagi district of Karnataka state was carried out. In Bt cotton many arthropod pest species belonging to orders like Lepidoptera, Homoptera, Hemiptera, Coleoptera etc were recorded. On the other hand, in Bt cotton agro-ecosystem many beneficial arthropod species are also reported such as Spined soldier bugs, Damsel bugs, Assassin bugs and other piercing and sucking predators like Lacewings, Ladybird beetle, Ground beetles, Parasitoid flies, Ichneumonid wasp, non-insect arthropods such as lynx spider and crab spider belonging to orders like Coleoptera, Neuroptera, Hemiptera, Hymenoptera, Lepidoptera and Araneae were recorded which predate on the egg and larva of pest species. The results showed that across the sampling months, seasonal variation existed in the abundance of beneficial arthropod communities in pesticide sprayed and unsprayed Bt cotton. The study also provided information on the adverse effect of pesticide drift both from plant run off and soil run off on the non-target beneficial arthropod species of cotton.